Hierarchical Ag nanostructures on Sn-doped indium oxide nano-branches: Super-hydrophobic surface for surface-enhanced Raman scattering - Min, Kyungchan; Choi, Kyoung Soon; Jeon, Wook Jin; Lee, Dong Kyu; Oh, Sein; Lee, Jouhahn; Choi, Jae Young; Yu, Hak Ki (RSC Advances, 2018)
Herein, we fabricated a super-hydrophobic SERS substrate using Sn-doped indium oxide (Indium-tin-oxide: ITO) nano-branches as a template. ITO nano-branches with tens of nanometer diameter are first fabricated through the vapor-liquid-solid (VLS) growth to provide roughness of the substrate. 10 nm thickness of Ag thin film was deposited and then treated with the post-annealing process to create numerous air-pockets in the Ag film, forming a hierarchical Ag nanostructures. The resulting substrate obtained Cassie's wetting property with a water contact angle of 151°. Compared to the normal hydrophobic Ag nanoparticle substrate, increase of about 4.25-fold higher SERS signal was obtained for 7 μL of rhodamine 6G aqueous solutions.
Keywords: Indium tin oxide; SERS substrate; Super-hydrophobic surfaces; Superhydrophobic; Surface enhanced Raman Scattering (SERS); Vapor-liquid-solid growth; Water contact angle; Wetting property